ANALISIS PENGARUH BRAND IMAGE DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE DENGAN KUALITAS PELAYANAN SEBAGAI VARIABEL MODERASI - Suprayitno, Dwi Haryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study was to analyze the significance of the influence of brand image, product attributes, and quality of service to mobile phone purchasing decisions Evercoss in Authorized Sales and Distributor Evercoss Solo. To analyze the effect of moderating the influence of service quality brand image and product attributes of the mobile phone purchasing decisions Evercoss in Authorized Sales and Distributor Evercoss Solo. In conclusion: Hypothesis 1 stated that: There is a significant influence on purchasing decisions brand image Evercoss mobile phones in the Authorized Sales and Distributor Evercoss Solo, unsubstantiated. Hypothesis 2 stated that: There is a significant influence on purchasing decisions product attributes Evercoss mobile phones in the Authorized Sales and Distributor Evercoss Solo, unsubstantiated. Hypothesis 3 which states that: There was a significant effect of service quality on the phone purchase decision Evercoss in Authorized Sales and Distributor Evercoss Solo. Hypothesis 4 which states that: The quality of service brand image moderating influence on purchasing decisions phone Evercoss in Authorized Sales and Distributor Evercoss Solo, not truth. Hypothesis 5, which states that: moderate the influence of service quality attributes of the product to the mobile phone purchasing decisions Evercoss in Authorized Sales and Distributor Evercoss Solo, not truth. Keywords: Brand Image, Product Attributes Quality Service, Mobile Buying Decision